Event Analysis; Analysis of Jeffery Dahmer (A.K.A Milwaukee Cannibal) - Addingi, Mwuese Titor (Journal of Historical Studies, 2022)
Sexual homicides, although rare attract a great deal of attention from the media, the general public, and, more recently, the academic community, they are devastating crimes and have the potential for repetition. A case study of Jeffery Dahmer, Milwaukee Cannibal sexual homicide was analyzed for the purpose of this research. Clinicians are often caught in the dilemma of helping offenders succeed in a society that will not allow them to achieve success and may actively conspire against successful reintegration. Despite the vast knowledge about serial killers, it is still uncertain why they kill. Undoubtedly, many factors enable individuals to perform such acts without remorse, including biological and neuropsychological factors, such as being bombarded by images that glamorize violence daily. Thus, the clinician/ social workers must struggle to find ways to help his or her clients practice their new skills in a society that does not want the offender and takes active steps to ostracize and humiliate offenders, which in turn leads to former offenders experiencing further isolation and a loss of hope.